The Resilience of Habitable Climates Around Circumbinary Stars. Issue 9 (16th September 2020) - Wolf, Eric T.; Haqq‐Misra, Jacob; Kopparapu, Ravi; Fauchez, Thomas J.; Welsh, William F.; Kane, Stephen R.; Kostov, Veselin; Eggl, Siegfried
Abstract: Here we use a 3‐D climate system model to study the habitability of Earth‐like planets orbiting in circumbinary systems. In the most extreme cases, Earth‐like planets in circumbinary systems could experience variations in the incident stellar flux of up to ~50% on ~100‐day timescales. However, we find that Earth‐like planets, having abundant surface liquid water, are generally effective at buffering against these time‐dependent changes in the stellar irradiation due to the high thermal inertia of oceans compared with the relatively short periods of circumbinary‐driven variations in the received stellar flux. Ocean surface temperatures exhibit little to no variation in time; however, land surfaces can experience modest changes in temperature, thus exhibiting an additional mode of climate variability driven by the circumbinary variations. Still, meaningful oscillations in surface temperatures are only found for circumbinary system architectures featuring the largest physically possible amplitudes in the stellar flux variation. In the most extreme cases, an Earth‐like planet could experience circumbinary‐driven variations in the global mean land surface temperature of up to ~5 K, and variations of local daytime maximum temperatures of up to ~12 K on seasonal timescales, while the global mean ocean temperatures vary by less than ~2 K. Such seasonal temperature swings over land areas could potentially pose adaptability challenges for extant life. Still, habitable planets in circumbinary systems appear to be remarkably resilient against circumbinary‐driven climate variations and can avoid any true climate catastrophes. Plain Language Summary: A circumbinary system is one where a planet orbits around two stars simultaneously, resulting in large and rapid changes to both the stellar energy distribution and the total stellar energy received by the planet. Planets in circumbinary systems can experience significant variations in their received stellar energy over ~10‐ to ~100‐day timescales. However, habitable planets in circumbinary systems are highly effective at buffering these changes in the received stellar energy due to the large thermal inertia of the oceans. Ocean surface temperatures exhibit little to no variation in time; however, land surfaces can experience modest changes in temperature. Even for the most extreme variations in stellar flux possible for circumbinary systems, Earth‐like planets could avoid a permanent climate catastrophe, such as a runaway greenhouse or glaciation. Key Points: Earth‐like planets in circumbinary systems are resilient against climate catastrophe, despite significant time‐dependent variations in the incident stellar flux While ocean temperatures are not appreciably affected, land surface temperatures can exhibit an additional mode of circumbinary‐seasonal variability Circumbinary systems should be considered as viable hosts for habitable worlds